A Study on Physical Education Outcomes and Motor Competence Based on Students’ Sports Interests in School Settings - Syahruddin, Syahruddin; Saleh, Muhammad Syahrul; Saleh, Muh. Sahib (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study investigates the relationship between sports interest, motor competence, and physical education outcomes in secondary school students. The primary aim was to examine how students' interest in sports influences their motor skills development and subsequent performance in physical education (PE) classes. A quantitative descriptive-correlational approach was employed, involving a sample of 300 students from six secondary schools. Data were collected through a Sports Interest Inventory, Motor Competence Assessment, and a Physical Education Outcomes Questionnaire. The results revealed a significant positive correlation between sports interest and motor competence, with students demonstrating higher levels of sports interest exhibiting better motor skills. Furthermore, students' sports interests and motor competence were found to significantly impact their engagement, skill achievement, and attitudes toward PE. The study highlights the importance of fostering sports interest in improving not only motor competence but also the overall experience and outcomes in PE. These findings emphasize the need for educators to consider students' interests and provide a variety of sports options to enhance engagement and motivation in physical education. The study’s results have important implications for curriculum development and teaching strategies, advocating for the integration of students' sports interests to support their physical and mental growth. Future research should explore the role of social influences, such as peer and family support, and employ longitudinal designs to further investigate the long-term effects of sports interest and motor competence on physical education outcomes.